Pemanfaatan paving blok sebagai bahan reduksi panas lingkungan - Mohammad Imran; Novita Shamin; Rahmi Budi As'Adiyah (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2020)
Global warming increases the overall temperature of the earth's surface and leads to climate change. Therefore, it plays an important impact on human life, especially in the architecture field. This study aims to identify the rise in environmental temperature due to parked cars with running engines and the use of paving blocks as heat-reducing material. This is a quantitative research with data collected and measured directly in the field, before being processed and explored of natural and waste materials in the laboratory. The results showed: (1) an increase in environmental temperature of ± 34.80C - 39.40C, or 50C to 100C due to parked cars with running engines, (2) the use of rectangular and hexagon paving blocks as heat-reducing material. Therefore, the increase in environmental temperature is reduced by the use of paving blocks, which comprises of basic (cement, sand, and water), natural (grass and fibers), and recycled materials (sawdust and styrofoam).